Peningkatan Pemahaman Peserta Didik Kelas IX tentang Kecerdasan Buatan melalui Sosialisasi Berdasarkan Hasil Pre-test dan Post-test di SMP Negeri 11 Samarinda (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The advancement of Artificial Intelligence technology has brought changes in various areas of life, one of which is the education sector. The ease of accessing applications such as ChatGPT opens up opportunities to support learning but at the same time presents challenges related to understanding and usage ethics. This activity aims to improve literacy and understanding of 45 students in class IX of SMP Negeri 11 Samarinda about the basic concepts, benefits, risks, and how to use AI wisely and responsibly. The method used is quantitative descriptive with data collection through pre-test and post-test. The activity is carried out through the delivery of materials, discussions, questions and answers, and the practice of preparing simple prompts with the theme "Smart AI, Not Cheating AI". Analysis using Wilcoxon Signed Ranks Test produces Z value = -3,530 and Asymp. Sig. (2-tailed) = 0,000 (p < 0,05), which indicates a significant difference between pre-test and post-test results. This activity supports the improvement of AI understanding as well as ethical awareness and academic honesty.